Sosialisasi, Edukasi dan Pendampingan Sertifikasi Halal melalui Platform Digital Sihalal bagi UMKM di Kecamatan Burneh Bangkalan - Moh Karim; Karim, Busro; Hasan, Mohammad; Kamil, Moh Ramdhan; Elliza Ramadhani, Rifda (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2024)
Halal certification is a business ethic that must be adhered to by MSMEs (producers) as a guarantee of halal food for consumers. The aim of this community service activity is to provide standard information that must be met by entrepreneurs; provide knowledge, benefits and awareness of the importance of Halal Certification for micro business actors' products as well as providing information and assistance on procedures for applying for Halal Certification for micro business actors in Burneh District, Bangkalan Regency to help and promote partners (MSMEs) in business development. The implementation method is by conducting outreach, education and mentoring on Halal Certification through the Sihalal Digital Platform to MSME actors. As a result of this community service activity, 30 business actors were assisted in applying for halal certification. Sihalal is one of the applications launched by the government to accelerate the halal certification application process in assisting partners (MSMEs) to apply for halal certification to support product competitiveness until MSME products obtain halal certificates. Assistance activities to obtain halal certificates are very important for the development of MSMEs, especially halal products that guarantee their production and distribution.